Analyzing Healthcare Attrition using Machine Learning and Traditional Statistical Techniques (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2026)
It is important to understand what might cause healthcare professionals to leave their jobs.  In this research, we therefore analyze data on employee attrition in the healthcare sector to determine which factors motivate these professionals to leave or stay in their current careers.  We combine the flexibility of machine learning techniques with the transparency of traditional statistical techniques, such as logistic regression analysis, to understand the data.  With an accuracy rate of 95.6%, based on several factors in this study, we find that one of the primary reasons these healthcare professionals leave their jobs is excessive overtime requirements.  Using a deeper analysis involving logistic regression, we determine the quantitative effects of our different explanatory variables.  We also find that job satisfaction does not seem to have as much explanatory power as several other variables, and that it does not seem to be a mediating variable in explaining attrition.